Uniformity Test Tablets Of Atorvastatin on the Market Using Ultraviolet Spectrophotometer - Sholichah Rohmani; Adi Yugatama; Ahmad Ainurofiq; Fea Prihapsara; Felicitas Lady (Universitas Sebelas Maret, 2017)
Atorvastatin is one of the first choice in the treatment of dyslipidemia associated with a decreased risk of cardiovascular disease. Drug patent expires in 2011. Currently in Indonesia circulated atorvastatin dosage tablet innovator , several trade names , and one generic. The purpose of this study was conducted to determine the quality of the preparation of atorvastatin market in Indonesia through tablet dosage uniformity test , so that the appropriate levels of drugs can provide the desired therapeutic effect.Uniformity tablet dosage form of atorvastatin is done by measuring the uniformity of tablet weight, and content uniformity was done using ultraviolet spectrophotometry in methanol at the maximum wavelength of 246.2 nm and their validity was tested on the value of LOD (limit of detection), and LOQ (limit of quantitation). One- Way ANOVA analyzis was their also conducted. The results showed that of the calculation data obtained , either in column A or column B that there is no deviation from the weight of the tablet , and based on the calculation of CV showed that all the tablets of atorvastatin in the market already qualified uniformity of weight as indicated by the value of CV < 5 %, and the levels atorvastatin tablet generic and tablets under the trade name meets the standard requirements of a tablet that in the range 90.0 % - 110.0 % of the amount listed on the label